Pengaruh Promosi Dan Customer Relationship Management Terhadap Kepuasan Nasabah Bank Mandiri Pada Penggunaan Mobile Banking Livin' By Mandiri (Studi Pada Bank Mandiri Cabang Tangerang City) - Ayu Deviyanti; Reza Khairul Hadi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the Effect of Promotion and Customer Relationship Management on Bank Mandiri Customer Satisfaction in the Use of Mobile Banking Livin 'By Mandiri (Study at Bank Mandiri Tangerang City Branch) both partially and simultaneously. The method used is quantitative associative. The sampling technique uses a purposive sampling method and obtained a sample of 109 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests with the help of SPSS software version 25. The results of the study indicate that partially the promotion variable has a positive but not significant effect on customer satisfaction, with a significance value of 0.030 (<0.05). Meanwhile, the customer relationship management variable has a positive and significant effect on customer satisfaction, with a significance value of 0.000 (<0.05). Simultaneously, promotion and customer relationship management have a significant effect on customer satisfaction with an F count value of 47.955 and a significance of 0.000 (<0.05). Thus, customer relationship management is the most dominant variable in increasing customer satisfaction of Livin' by Mandiri users at Bank Mandiri Tangerang City branch